Stories we tell [videorecording (DVD)] - Polley, Sarah; Polley, Michael; Buchan, John, 1875-1940; Butler, Tom; Bigelow, Pixie (Lionsgate, 2013)
In this inspired, genre-twisting film, Oscar-nominated writer/director Sarah Polley discovers that the truth depends on who's telling it. Polley is both filmmaker and detective as she investigates the secrets behind a family of storytellers. She playfully interviews and interrogates a cast of characters of varying reliability, eliciting refreshingly candid, yet mostly contradictory, answers to the same questions.